Existence of periodic solutions for a class of p-Hamiltonian systems - Heidari Tavani, Mohammad Reza (Eurasian Mathematical Journal, 2018)
Based on some variational methods for smooth functionals defined on reflexive Banach spaces, the existence of periodic solutions for a class of \( p \)-Hamiltonian systems is established.